Analisis Proses Pelayanan Ijin Mendirikan Bangunan Di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Semarang - Hermawan Sadewa; Puji Astuti (Journal of Politic and Government Studies, 2018)
This study aims to determine the licensing process permit Building Permit. In this study, the authors will choose to focus on the process of building permit building (IMB) service in the Integrated Licensing Service Office of Semarang City because Building Permit (IMB) is the most widely served licenses. This raises several issues that can be studied, namely how the service creation process Building Permit provided by the Department of Investment and Integrated Services One Door Semarang City? Is the licensing service process of Building Permit in the Office of Investment and Integrated Services One Door of Semarang City in accordance with the Standard Operating Companies?This research uses qualitative method with descriptive approach which only describes, summarizes various condition, situation or various variable. This research approach using qualitative approach, because in this research target or object of research is limited so that data that can be dug as much as possible and not possible existence of widening of research object. In this research, we will describe the concrete condition of the research object, connecting one variable or condition with other condition variable and then will be generated description about research object.The result of the research shows that IMB licensing service system at One Stop Service Office of Investment and Service of Semarang City has experienced a more positive improvement seen from the simpler licensing service mechanism applied in DPM-PTSP Semarang City, however, in the process of Building Permit Services in DPM-PTSP Semarang City there are many factors.Key words: Analysis of Service Process, Building Permit Service, DPM-PTSP Semarang City